2023
DOI: 10.1037/fam0001066
|View full text |Cite
|
Sign up to set email alerts
|

Parental sensitivity predicts parent–adolescent agreement about peer victimization.

Abstract: Effective parental responses to peer victimization may hinge on parental awareness of youths’ peer victimization experiences, yet predictors of parental awareness are understudied. We investigated the extent of parent–adolescent agreement about early adolescents’ peer victimization experiences as well as predictors of parent–adolescent agreement. Participants included a diverse community sample of early adolescents (N = 80; Mage = 12.36 years, SD = 1.33; 55% Black, 42.5% White, 2.5% other race/ethnicity) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…This was evident in participants’ responses in this study. Moreover, parents in the study reported a high degree of sensitivity in detection of behavioral and emotional cues about problematic peer experiences that were not explicitly expressed by their child (see also VanDenBerg et al, under review). This prompted increased communication and facilitated disclosure by the early adolescent.…”
Section: Discussionmentioning
confidence: 99%
“…This was evident in participants’ responses in this study. Moreover, parents in the study reported a high degree of sensitivity in detection of behavioral and emotional cues about problematic peer experiences that were not explicitly expressed by their child (see also VanDenBerg et al, under review). This prompted increased communication and facilitated disclosure by the early adolescent.…”
Section: Discussionmentioning
confidence: 99%